Age‐related neuromuscular changes affecting human vastus lateralis. (15th December 2015) - Piasecki, M.; Ireland, A.; Stashuk, D.; Hamilton‐Wright, A.; Jones, D. A.; McPhee, J. S.
Abstract : Key points: Skeletal muscle size and strength decline in older age. The vastus lateralis, a large thigh muscle, undergoes extensive neuromuscular remodelling in healthy ageing, as characterized by a loss of motor neurons, enlargement of surviving motor units and instability of neuromuscular junction transmission. The loss of motor axons and changes to motor unit potential transmission precede a clinically‐relevant loss of muscle mass and function. Abstract: The anterior thigh muscles are particularly susceptible to muscle loss and weakness during ageing, although how this is associated with changes to neuromuscular structure and function in terms of motor unit (MU) number, size and MU potential (MUP) stability remains unclear. Intramuscular (I.M.) and surface electromyographic signals were recorded from the vastus lateralis (VL) during voluntary contractions held at 25% maximal knee extensor strength in 22 young (mean ± SD, 25.3 ± 4.8 years) and 20 physically active older men (71.4 ± 6.2 years). MUP size, firing rates, phases, turns and near fibre (NF) jiggle were determined and MU number estimates (MUNEs) were made by comparing average surface MUP with maximal electrically‐evoked compound muscle action potentials. Quadriceps cross‐sectional area was measured by magnetic resonance imaging. In total, 379 individual MUs were sampled in younger men and 346 in older men. Compared to the MU in younger participants, those in older participants had 8% lower firing rates and larger MUP size (+25%), as well as increased complexity, as indicated by phases (+13%), turns (+20%) and NF jiggle (+11%) (all P  < 0.0005). The MUNE values (derived from the area of muscle in range of the surface‐electrode) in older participants were ∼70% of those in the young ( P  < 0.05). Taking into consideration the 30% smaller cross‐sectional area of the VL, the total number of MUs in the older muscles was between 50% and 60% lower compared to in young muscles ( P  < 0.0005). A large portion of the VL MU pool is lost in older men and those recruited during moderate intensity contractions were enlarged and less stable. These MU changes were evident before clinically relevant changes to muscle function were apparent; nevertheless, the changes in MU number and size are probably a prelude to future movement problems. Key points: Skeletal muscle size and strength decline in older age. The vastus lateralis, a large thigh muscle, undergoes extensive neuromuscular remodelling in healthy ageing, as characterized by a loss of motor neurons, enlargement of surviving motor units and instability of neuromuscular junction transmission. The loss of motor axons and changes to motor unit potential transmission precede a clinically‐relevant loss of muscle mass and function.